Describing the Dynamics of Meiobenthic Assemblages Regarding Factors of Environmental by Determining the Temporal Variations: Temporal variations and environmental factors influencing meiobenthic assemblages in a sandy intertidal zone (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Sandy intertidal zones were dissected for the nearness of meiofauna. The meiofauna (here characterized as metazoans which estimate go from 50 to 500 ìm) is a faunal gathering of high significance in the working of estuarine frameworks, particularly where soft bottoms prevail and the issue and energy fluxes start for the most part from the benthic detrital complex The present paper portrays the elements of meiobenthic collections in connection to natural factors along the shore of Thiruvananthapuram, Kerala on the southwest coast of India. Meiobenthic people group comprised of 11 taxa in which nematodes, foraminifers and copepods ruled. Impressive transient variations are recognizable for all meiofaunal taxa. The surrounding physico-chemical states of water and physical changes in sediment are in charge of the temporal distribution of meiobenthos. Vertically a descending movement of meiofauna has been seen in the sand section because of better waste, high atmospheric temperature and presentation.